2020
DOI: 10.1002/lary.28953
|View full text |Cite
|
Sign up to set email alerts
|

Management of A‐Frame Tracheal Deformity in Children With Endoscopic Resection Tracheoplasty

Abstract: Objectives Tracheal A‐frame deformity is a known consequence of tracheostomy that may lead to obstruction after decannulation. The goal of this study is to demonstrate the feasibility and success of endoscopic carbon dioxide (CO2) laser‐assisted tracheoplasty of tracheal A‐frame deformity in children. Methods Retrospective case series of symptomatic children with tracheal A‐frame deformity with no other site of airway obstruction (2016–2018). All patients underwent CO2‐laser assisted endoscopic resection trach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In the localization of tracheal stenosis, the minimum tracheal area was seen at the proximal and distal locations at BL, where there might be difficulty with intubation, even in patients without stenosis. After tracheostomy, the minimum tracheal area was predominantly observed above the tracheostomy site, consistent with prior reports examining symptomatic tracheal stenosis or deformity by endoscopy ( 6 , 12 ). On the other hand, the maximum area was broadly distributed across the trachea at BL.…”
Section: Tracheal Stenosis – Decreased Area After Tracheostomysupporting
confidence: 88%
See 1 more Smart Citation
“…In the localization of tracheal stenosis, the minimum tracheal area was seen at the proximal and distal locations at BL, where there might be difficulty with intubation, even in patients without stenosis. After tracheostomy, the minimum tracheal area was predominantly observed above the tracheostomy site, consistent with prior reports examining symptomatic tracheal stenosis or deformity by endoscopy ( 6 , 12 ). On the other hand, the maximum area was broadly distributed across the trachea at BL.…”
Section: Tracheal Stenosis – Decreased Area After Tracheostomysupporting
confidence: 88%
“…In most reports regarding tracheostomy, bronchoscopy has been used to assess for tracheal stenosis ( 12 ). However, detailed changes in tracheal diameter by numerical value cannot be measured by bronchoscopy, and it is relatively invasive compared to CT ( 13 – 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the patients who require revision surgery, A-frames are less amenable to treatments such as balloon dilation and stent placement and frequently require aggressive laser-based endoscopic interventions, resection with end-to-end anastomosis, anterior graft LTR, or slide tracheoplasty. 9,15,16 In this study, the most important factor related to development of an A-frame deformity was the history of tracheostomy. From the population of children who developed this deformity, only one did not have a tracheostomy.…”
Section: Discussionmentioning
confidence: 85%
“…5 Anecdotal success of nebulized CPD has been reported for airway foreign body retrieval 13 , laryngeal trauma management 14 , tracheoplasty and tracheal resection 8 , and endoscopic airway management in children. 4,16 Notably, in our survey, a significantly greater percentage of respondents practicing for <10 years use nebulized CPD compared to those practicing for >10 years. This trend may be explained by greater exposure to offlabel CPD use for pediatric otolaryngologists who completed training more recently.…”
Section: Discussionmentioning
confidence: 68%
“…4 Studies have reported dosing nebulized CPD at 1 mL (20 drops) and 0.5 mL (10 drops) in 1 mL normal saline 2-3 times daily for 7 days after tracheal surgery for patients ≥2 years-old and <2 years-old, respectively. 4,8,12,16 Each mL of CPD contains 3 mg ciprofloxacin and 1 mg dexamethasone; one drop contains 0.04 mg ciprofloxacin and 0.11 mg dexamethasone. 5 Anecdotal success of nebulized CPD has been reported for airway foreign body retrieval 13 , laryngeal trauma management 14 , tracheoplasty and tracheal resection 8 , and endoscopic airway management in children.…”
Section: Discussionmentioning
confidence: 99%